Enzymatic and transcriptomic analysis reveals the essential role of carbohydrate metabolism in freesia (Freesia hybrida) corm formation - Li Ma; Suqin Ding; Xueqing Fu; Zi Yan; Dongqin Tang (PeerJ, 2021)
Starch and sucrose metabolism plays a crucial role in the formation and development of bulbs in bulbous plants. However, these mechanisms remain unclear and unexplored in the corms of Freesia hybrida. Herein, we investigated the dynamics of the major form of carbohydrates and related enzyme activities and profiled the transcriptome of freesia corms at four developmental stages with the aim to reveal the relation between the expression of genes involved in the metabolism of carbohydrates and the accumulation of carbohydrates in corm developmental stages for further exploring the mechanism on the starch and sucrose metabolism regulating the formation and development of corms in F. hybrida. The content of starch, sucrose and soluble sugars followed an overall upward trend across the corm developmental stages. Activities of the adenosine diphosphoglucose pyrophosphorylase, starch branching enzyme and β-amylase generally followed the pattern of the starch and sucrose levels. Activities of sucrose phosphate synthase increased from corm formation till the initial swelling stage and subsequently reached a plateau. Activities of invertase and sucrose synthase peaked at the later rapid swelling stage. These suggested that the starch and sucrose dynamics paralleled corm swelling under the action of metabolic enzymes. A total of 100,999 unigenes were assembled in the transcriptomic analysis, and 44,405 unigenes of them were annotated. Analysis based on Clusters of Orthologous Groups suggested that carbohydrate transport and metabolism (9.34% of the sequences) was prominent across the corm developmental process. In total 3,427 differentially expressed genes (DEGs) were identified and the enrichment analysis detected starch and sucrose metabolism as a critical pathway in corm development, especially at the rapid swelling stage. Further, DEGs encoding key carbohydrate-metabolizing enzymes were identified and correlated to enzyme activities and carbohydrate accumulation. The results construct a valuable resource pool for further molecular-level studies, which are helpful for metabolic regulation of carbohydrates and improvement in F. hybrida.